2010
DOI: 10.1063/1.3430640
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless magnetic reconnection in the presence of a sheared velocity field

Abstract: Physics of Fluids, 17, p. 062102 (2010)International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Finding #2 in Table 2 points out that the spectral breakpoint is associated with the thicknesses of current sheets in the solar wind. As noted in Table 2, physical processes that act on the thicknesses of current sheets are important, such as plasma expansion and compression (Schindler & Hesse, 2008, 2010, Bohm and gyro-Bohm diffusion (Borovsky, 2006;Borovsky & Gary, 2009;Pecseli & Mikkelsen, 1985;Perkins et al, 1993;Vahala & Montgomery, 1971), eddy diffusion (Borovsky, 2006;Chen & Montgomery, 1987;Yoshizawa & Yokoi, 1996), Alfvén wave steepening (Tsurutani & Ho, 1999;Vasquez & Hollweg, 2001), current sheet instabilities (Birn et al, 2004;Daughton, 2003;Roytershteyn & Daughton, 2008), and reconnection (Faganello et al, 2010;Gosling & Phan, 2013;Yin & Winske, 2002).…”
Section: 1029/2019ja027307mentioning
confidence: 99%
“…Finding #2 in Table 2 points out that the spectral breakpoint is associated with the thicknesses of current sheets in the solar wind. As noted in Table 2, physical processes that act on the thicknesses of current sheets are important, such as plasma expansion and compression (Schindler & Hesse, 2008, 2010, Bohm and gyro-Bohm diffusion (Borovsky, 2006;Borovsky & Gary, 2009;Pecseli & Mikkelsen, 1985;Perkins et al, 1993;Vahala & Montgomery, 1971), eddy diffusion (Borovsky, 2006;Chen & Montgomery, 1987;Yoshizawa & Yokoi, 1996), Alfvén wave steepening (Tsurutani & Ho, 1999;Vasquez & Hollweg, 2001), current sheet instabilities (Birn et al, 2004;Daughton, 2003;Roytershteyn & Daughton, 2008), and reconnection (Faganello et al, 2010;Gosling & Phan, 2013;Yin & Winske, 2002).…”
Section: 1029/2019ja027307mentioning
confidence: 99%
“…This diffusivity has been linked to faster reconnection rates although the existence of the instability is still controversial ). (d) Kelvin-Helmholtz instabilities in thin sheared current sheets may also lead to reconnection (Faganello et al 2010;. (e) An ion firehose instability driven in the ion-diffusion region by counterstreamingion-beams in the ion-diffusion region during anti-parallel reconnection .…”
Section: Measures Of Diffusion Regionsmentioning
confidence: 99%
“…In these conditions, previous studies have demonstrated that the nonlinear evolution of KH vortices enables the occurrence of magnetic reconnection driven by large-scale vortex motions, of interest for space plasmas [7][8][9][10] , as well as for astrophysical plasmas jets 11,12 . The vortex formation process indeed drags the magnetic field component parallel to the solar wind direction into the flow.…”
Section: Introductionmentioning
confidence: 99%